Pergeseran Tindak Berbahasa Mahasiswa dalam Komunikasi Formal dan Informal di Tengah Perkembangan Digital - Neyarasmi, Fadilah; Musyawir, Musyawir (Magister Pendidikan Bahasa dan Sastra Indonesia Universitas Jambi, 2025)
The digital era has changed the way students communicate, both in formal situations such as online lectures and informally on social media. This study aims to find out the students' language shift between formal and informal situations and the digital factors that influence it. The method used is a qualitative study with multiple case studies. Data were obtained from observation, in-depth interviews, and analysis of communication documents of 20 students of Makassar State University. The results showed that students often code-switch and mix languages, depending on the social context, the need for quick communication, and the digital platform used. In formal situations, they still use standard language although they sometimes insert digital abbreviations. While in informal situations, the use of emoticons, abbreviations, and local language mixtures are more dominant. These findings emphasize the importance of digital literacy and pragmatic language training in the college curriculum, so that students are able to adjust language as needed.